ENABLE BUSINESS RISK, DEBT POLICY, GROWTH OPPORTUNITY, DIVIDEND PAYOUT RATIO, AND CASH HOLDING TO STRENGTHEN THE FIRM VALUE - Sriyono Sriyono; Dinda Ayu Ramadhani (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2023)
To attract more investors, the company's management must increase the value of the company. There have been many studies that have been done before, however, research that uses all aspects does not yet exist. This study aims to determine the effect of Business Risk, Debt Policy, Growth Opportunity, Dividend Payout Ratio, and Cash Holding on Firm Value Sector Companies Property, Real Estate, and Construction Listed on the IDX in 2019-2020. This study uses a quantitative method and the object of this research is the population of all Properties, Real Estate, and Construction listed on the IDX for the 2019-2020 period, and the sampling technique uses the purposive sampling method. The data collection technique uses the company's annual report from the 2019-2020 period. The analytical technique used in this study is path analysis with the help of the Eviews 9 program. The conclusion is Business Risk, Dividend Payout Ratio has no significant effect on firm value, debt policy, and Growth Opportunity has a significant positive effect on firm value.